Cannabidiol usage, efficacy, and side effects: analyzing the impact of health conditions, medications, and cannabis use in a cross-sectional online pilot study - Binkowska, Alicja Anna; Jakubowska, Natalia; Redeł, Anna; Laskowska, Sandra; Szlufik, Stanisław; Brzezicka, Aneta (Frontiers in Psychiatry, 2024)
Background: Products containing cannabidiol (CBD) are attracting attention because of their potential therapeutic benefits and positive impacts on well-being and mental health. Although additional research is needed to understand their effectiveness in treating mental disorders, cross-sectional studies may help identify the factors influencing CBD use patterns. This study examined the impact of variables such as health status, medication use, medical supervision, gender, age, and cannabis use on CBD consumption patterns.A self-selected sample (n =267) of current or former CBD users was recruited via social media and participated in an online survey designed to collect data on basic demographics, health status, cannabis use, and CBD usage patterns.The sample (n = 267) consisted of 68.5% women with an average age of 30.21 years,of which 25.8% reported diagnosed psychiatric disorders and 49.4% reported cannabis use. The top five reasons for using CBD were self-reported stress (65.3%), sleep problems (51.7%), overall improvement in well-being (52.5%), improved mood (44.9%), and anxiety relief (40.9%). Our findings suggest that individuals with psychiatric disorders and those taking psychotropic medications are more likely to use CBD to relieve stress and anxiety. Overall, nearly 70% of the individuals found CBD products to be effective. Sublingual administration was more popular among non-cannabis users, while cannabis users preferred smoking and vaping to CBD administration.Our results indicate that individuals using CBD for health and wellness reasons believe that it has potential health benefits. Further research using rigorous longitudinal designs is needed to delve deeper into the effectiveness of low-dose CBD and to better understand the therapeutic potential of CBD.